2005
DOI: 10.1111/j.1472-765x.2005.01738.x
|View full text |Cite
|
Sign up to set email alerts
|

The uses of AFLP for detecting DNA polymorphism, genotype identification and genetic diversity between yeasts isolated from Mexican agave-distilled beverages and from grape musts

Abstract: Aims:The objectives were to determine the variability and to compare the genetic diversity obtained using amplified fragment length polymorphism (AFLP) markers in analyses of wine, tequila, mezcal, sotol and raicilla yeasts. Methods and Results: A molecular characterization of yeasts isolated from Mexican agave musts, has been performed by AFLP marker analysis, using reference wine strains from Italian and South African regions. Conclusions: A direct co-relation between genetic profile, origin and fermentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 24 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Flores Berrios et al . (2005) used amplified fragment length polymorphism (AFLP) to detect DNA polymorphism, genotype identification, and genetic diversity between S. cerevisiae, Candida spp., and Hanseniaspora spp.…”
Section: Yeast In the Fermentation Processmentioning
confidence: 99%
“…Flores Berrios et al . (2005) used amplified fragment length polymorphism (AFLP) to detect DNA polymorphism, genotype identification, and genetic diversity between S. cerevisiae, Candida spp., and Hanseniaspora spp.…”
Section: Yeast In the Fermentation Processmentioning
confidence: 99%
“…(1999). Flores‐Berrios et al. (2006) used the amplified fragment length polymorphism (AFLP) technique to study the genetic yeast diversity, and showed the underlying relationship between the molecular profiles, strain origin and fermentation process for yeast isolated from Mexican agave spirit (tequila, raicilla, sotol and mezcal), Italian and African wines.…”
Section: Introductionmentioning
confidence: 99%
“…The electrophoretic profiles detected by these techniques did not allow a clear differentiation between the strains used possibly because the strains that are collected in the same geographic region show a similar genomic constitution (9, 18, 37). However, interdelta fingerprinting was an adequate technique to identify differences between parental strains as well as between the hybrids obtained and their parental strains.…”
Section: Discussionmentioning
confidence: 99%